TỐC ĐỘ CHUYỂN DỊCH KIẾN TẠO GIAI ĐOẠN PLEISTOCEN GIỮA - MUỘN DỌC ĐỚI ĐỨT GÃY SÔNG HỒNG KHU VỰC LÀO CAI - VIỆT TRÌ - Liêm, Ngô Văn; Trịnh, Phan Trọng; Vinh, Hoàng Quang; Hướng, Nguyễn Văn (Vietnam Journal of Earth Sciences, 2012)
SUMMARY Slip rates during the Middle-Late Pleistocene period along Red River Fault Zone in Lao Cai - Viet Tri section The Red River Fault Zone (RRFZ) is one of the major faults, which plays an important role in Asia as well as in Vietnam. In the Cenozoic, the RRFZ has been undergone two stages of motion: left-lateral displacement in Oligo-Miocene time and right-lateral displacement from Pliocene to present. This study presents new evidences on right-lateral displacement showned by the offsets of terraces, streams, Quaternary sediments and weathering layer,… along the RRFZ from Lao Cai to Viet Tri area. These offsets are determined in the Middle-Late Pleistocene period with the amount of right-lateral slip is estimated from 100m to 1300m and the slip rate from 1.1mm/yr to 1.8mm/yr.